Determinants of students' success at university - Kamila Danilowicz-Gösele; Johannes Meya; Robert Schwager; Katharina Suntheim (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
This paper studies the determinants of academic success using a unique administrative data set of a German university. We show that high school grades are strongly associated with both graduation probabilities and final grades, whereas variables measuring social origin or income have only a smaller impact. Moreover, the link between high school performance and university success is shown to vary substantially across faculties. In some fields of study, the probability of graduating is rather low, while grades are quite good conditional on high school performance. In others, weaker students have a greater chance of graduating, but grades are more differentiated.
Keywords: I23; I21; 330; university; high school; grade point average; faculties; education